2019
DOI: 10.3389/fbioe.2019.00190
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-Coated Electrospun Regenerated Silk Fibroin Mats Promote Neural Progenitor Cell Proliferation, Differentiation, and Survival in vitro

Abstract: Neural progenitor cell (NPC) transplantation is a promising technique for central nervous system (CNS) reconstruction and regeneration. Biomaterial scaffolds, frameworks, and platforms can support NPC proliferation and differentiation in vitro as well as serve as a temporary extracellular matrix after transplantation. However, further applications of biomaterials require improved biological attributes. Silk fibroin (SF), which is produced by Bombyx mori , is a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 75 publications
0
35
0
Order By: Relevance
“…LN is a primary component of the basement membrane and heavily involved in nerve regeneration 19 , 20 . LN is secreted by SCs and acts as an adhesive component that promotes the regenerative capacity of basal lamina scaffolds following nerve injury, with previous studies demonstrating its ability to promote neuritogenesis in vitro and in vivo 21 , 22 . Several fragments of the LN sequence were recently identified and tested for their potential bioactivity, with IKVAV (Ile-Lys-Val-Ala-Val) shown to selectively promote SC migration in vitro and capable of easy conjugation to SAPs 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…LN is a primary component of the basement membrane and heavily involved in nerve regeneration 19 , 20 . LN is secreted by SCs and acts as an adhesive component that promotes the regenerative capacity of basal lamina scaffolds following nerve injury, with previous studies demonstrating its ability to promote neuritogenesis in vitro and in vivo 21 , 22 . Several fragments of the LN sequence were recently identified and tested for their potential bioactivity, with IKVAV (Ile-Lys-Val-Ala-Val) shown to selectively promote SC migration in vitro and capable of easy conjugation to SAPs 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The topography of these materials influences the mechanosensory apparatus and the spatiotemporal dynamics of the cells ( Chen et al, 2014 ), and these cell-material interactions play a key factor in cell behavior regulation ( Guilak et al, 2009 ; Zangi et al, 2016 ). Many kinds of biomaterials have been investigated for guiding cell growth through topography, including nanofibers ( Liu et al, 2010 ; Xie et al, 2014 ; Omidinia-Anarkoli et al, 2017 ; Zuidema et al, 2018 ; Li et al, 2019 ), colloidal nanoparticles ( Antman-Passig et al, 2017 ; Musoke-Zawedde and Shoichet, 2006 ), and inverse opal materials ( Lu et al, 2014 ; Shang et al, 2019 ; Li et al, 2020 ). Among the applied biomaterials, inverse opal materials represent a class of porous structures with an ordered array of uniform nanoscale or microscale pores, which possessed well-controlled pore size, long-range ordered structure, and homogeneous interconnectivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mammals only have very limited HC regeneration ability; most of the damaged HCs cannot be spontaneously regenerated, which make the HC loss and hearing loss to be irreversible [58][59][60][61][62]. CIs are the most efficient clinical therapeutic devices for sensorineural deafness patients, and recent studies have shown that application of CI-based electric acoustic stimulation together with multiple biomaterials also can promote the differentiation of neural stem cell [63][64][65][66] and promote maturation of spiral ganglion neuron [67][68][69][70]. However, the neurophysiological study of musical pitch identification in CI users is still lacking in the hearing research field.…”
Section: Discussionmentioning
confidence: 99%